Unsymmetrical design and operation in counter-flow microfluidic fuel cell: A prospective study. (1st January 2023) - Li, Li; Wang, Hongkang; Bei, Shaoyi; Li, Yuanjiang; Sun, Yanyun; Zheng, Keqing; Xu, Qiang
Abstract: Performance of counter-flow microfluidic fuel cell is severely limited by the uneven current density distribution within the electrodes. In this work, in-depth numerical investigations are performed to examine the prospects of unsymmetrical design and operation in an all-vanadium counter-flow microfluidic fuel cell with flow-through electrodes to better utilize the electrode effective zone considering the anode-cathode mismatch on the mass transfer and electrochemical kinetics. Results indicate that size and position of the electrode effective zone vary under different operation conditions. Longer electrodes are required when the electrolyte flow rate or reactant concentration decreases. Optimized cathode length is smaller than its anode counterpart due to the faster diffusion rate of the oxidant and improved electrochemical reaction rate at the cathode. Concentration-related activation loss is found to play a key role in the performance of counter-flow microfluidic fuel cells and consequently, unequal initial flow rates are preferred in the cell operation to unequal initial reactant concentrations. Catholyte flow rate could be safely reduced to half of that in the anode with 95% retention of the output current, bringing a reduction of 50% in the catholyte consumption. The present findings could provide useful guidance for the future development of counter-flow microfluidic fuel cells. Highlights: Sizes and positions of electrode effective zones under various operation conditions are elucidated. Prospects of unsymmetrical design and operation in counter-flow MFC are identified. Unequal initial flow rates are preferred to unequal initial reactant concentrations.